2022
DOI: 10.2991/absr.k.220101.019
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production from Spent Coffee Grounds Oil

Abstract: Biodiesel has been considered as an alternative fuel to replace conventional oil in the world. Biodiesel development has reached blending for 30% and has been implemented by Indonesia since 2020. Sources for biodiesel production vary, as is well known, mostly from CPO, raw vegetable oil, used cooking oil, and animal fats. The utilization of waste as raw material for biodiesel can provide additional energy while reducing the amount of existing waste. Spent coffee grounds is an alternative raw material for biodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Pentadecanoic acid (CAS) Pentadecylic acid appeared at peak 9 have retention time 19.044 and an area of 19.91% at Figure 5. Research conducted by Chuaca et al (2022) also found the same components in coffee oil compositions from RTD coffee, with the retention time of 17.525 and area of 2.72%. Pentadecanoic acid was also found in Arabica coffee bean oil at a retention time of 19,151 and an area of 4.08%.…”
Section: Identification Of the Bukanagara Arabica Coffee Oil Metaboli...mentioning
confidence: 64%
See 2 more Smart Citations
“…Pentadecanoic acid (CAS) Pentadecylic acid appeared at peak 9 have retention time 19.044 and an area of 19.91% at Figure 5. Research conducted by Chuaca et al (2022) also found the same components in coffee oil compositions from RTD coffee, with the retention time of 17.525 and area of 2.72%. Pentadecanoic acid was also found in Arabica coffee bean oil at a retention time of 19,151 and an area of 4.08%.…”
Section: Identification Of the Bukanagara Arabica Coffee Oil Metaboli...mentioning
confidence: 64%
“…Nugraha et al (2020) stated that on ari's coffee beans also contained hexadecanoic acid at a retention time of 16,196 and an area of 11.48%. Chuaca et al (2022) also stated in coffee oil compositions from freshly brewed coffee there was also a retention time of 11,396 and an area of 0.02% and retention time of 11,277 and an area of 1.05% at coffee oil compositions from RTD coffee. This compound was a fatty acid found in both arabica and robusta coffee oil extracts, besides palmitic acid is found in green beans coffee and roasted beans coffee.…”
Section: Figure 5 Fragmentation Patterns Pentadecanoic Acid (Cas) Pen...mentioning
confidence: 75%
See 1 more Smart Citation
“…These examples demonstrate the difficulties that coffee businesses confront while procuring raw supplies and the resulting influence on pricing methods. Chuaca et al (Chuaca et al, 2022) and Nurani et al (Nurani et al, 2022) explore the impact of raw material availability and manufacturing costs on coffee product pricing. Coffee businesses frequently experience difficulties due to insufficient raw supplies and expensive fees.…”
Section: B Fluctuations In Raw Materials Pricesmentioning
confidence: 99%
“…However, biodiesel is still less economical when compared to petroleum diesel [31,32]. One of the raw materials for making biodiesel in Indonesia is coffee beans [33]. Indonesia is the fourth largest coffee producing country, after Brazil, Vietnam, and Columbia [34].…”
Section: Coffee and Biodieselmentioning
confidence: 99%